EFFECTS OF ETHANOL BLENDED DIESEL FUEL ON EXHAUST EMISSIONS FROM A DIESEL ENGINE - Özer CAN; İsmet ÇELİKTEN; Nazım USTA (Pamukkale University Journal of Engineering Sciences, 2005)
Diesel engine emissions can be improved by adding organic oxygenated compounds to the No. 2 diesel fuel. In this study, effects of 10 % and 15 % (in volume) ethanol addition to Diesel No. 2 on exhaust emissions from an indirect injection turbocharged diesel engine running at different engine speeds and loads were investigated. Experimental results showed that the ethanol addition reduced CO, soot and SO2 emissions, although it caused some increase in NOx emission and some power reductions due to lower heating value of ethanol. Improvements on emissions were more significant at full load rather than at partial loads.